Innovation of Riffaa D’hati concealer using the implementation of augmented reality technology and QR code / NurFatin Nabila Che Mad Fauzi ... [et al.] - Che Mad Fauzi, NurFatin Nabila; Omar, Mastura; Mohd Rosnan, Shalida; Abdul Rani, Mohd Khairul Azahari; Shamsuddin, Nik Atilla Atasha (Universiti Teknologi MARA, Kedah, 2023)
According to Puan Wan Fatimah Binti Megat Saad, Riffaa Group Sdn Bhd started operating on a small scale in January 2018 and only did a business on a small scale and only had a clothing boutique and growing rapidly by selling beauty products. Creative packaging involves state-of-the-art designs and solutions that not only help the product to stand out above the rest but also increase the product’s growth and success. The function of the packaging is to protect and prevent physical damage such as knocking, shaking, or crushing. Therefore, the packaging has become something to be displayed and has something to value in its own right because it has its own prestige. Not only that but the new packaging of Riffaa D’hati concealer also provides a more sustainable and cost-effective option throughout the lifespan of the package after the product is packed. The product Riffaa D’hati concealer is an organic cosmetic product that offers a variety of benefits for the skin because it uses organic ingredients. The purpose of the package is to create new packaging for concealer Riffaa and brush to improve marketing products. An innovative printed solution is developed with the integration of Augmented Reality (AR), it enables playable videos and creates an ID as a link between the video and the packaging. Additionally, a Quick Response (QR) code is added and placed on the Riffaa D’hati Concealer packaging box where customers can easily scan using their phones to find out the location of the Riffaa company. With the packaging upgrade, the product will be better known to consumers.